2022
DOI: 10.1002/mame.202100654
|View full text |Cite
|
Sign up to set email alerts
|

MoS2@PDA@Ag/PVA Hybrid Hydrogel with Excellent Light‐Responsive Antibacterial Activity and Enhanced Mechanical Properties for Wound Dressing

Abstract: Hydrogel is an ideal wound dressing material because of its 3D network structure, which is similar to that of the extracellular matrix. However, it is a challenge to design antibiotic-free hydrogels with both antibacterial activity and enhanced mechanical strength. In this study, a polyvinyl alcohol (PVA) hybrid hydrogel incorporated with molybdenum disulfide@polydopamine@silver (MoS 2 @PDA@Ag) is prepared for rapid killing of bacteria under irradiation with near-infrared (NIR) light. The interpenetration of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…101 Similarly, Tang's group prepared a MoS 2 @P-DA@Ag/PVA antibacterial hydrogel by freeze-thaw cycling, and the as-prepared hydrogel killed bacteria by PTT. 102 Fig. 9a indicates the self-healing ability of PSCMo hydrogels.…”
Section: Synthetic Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…101 Similarly, Tang's group prepared a MoS 2 @P-DA@Ag/PVA antibacterial hydrogel by freeze-thaw cycling, and the as-prepared hydrogel killed bacteria by PTT. 102 Fig. 9a indicates the self-healing ability of PSCMo hydrogels.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…By combining PTT and PDT, MoS 2 can generate ROS and transform light into heat, and combination treatment of PTT and PDT produces more ROS. 102 In recent years, antibacterial hydrogels based on MoS 2 , including PDMoT, MoS 2 @CNT, MoS 2 @PDA@Ag/PVA, Ag 3 PO 4 /MoS 2 , CuS@MoS 2 , and CFMG hydrogels, were proven to produce ROS ( OH and O 2 ) after PTT stimulation. 48,49,85,100,102,132 In 2021, Fan's group reported that by combining PTT and PDT, the PVA/Dex/MoS 2 @TA/Fe nanozyme-anchored multifunctional hydrogel (PDMoT) group had a lower abundance of E. coli and S. aureus compared with that of the PVA/Dex (PD) and PVA/Dex/MoS 2 (PDMo) groups.…”
Section: Ptt/pdt Combined Antibacterial Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, an intermediate healing rate was observed with their hydrogel without irradiation, hydrogel alone, or hydrogel with nanosheets without irradiation 114 . Yan et al prepared a PVA hydrogel incorporating molybdenum disulfide (MoS 2 )‐polydopamine‐AgNPs (7.5 mg/mL), observing that MoS 2 and polydopamine enhanced the strength of their PVA hydrogels 110 . The authors investigated a mixed microbial wound infection model in Kunming mice, wherein both S. aureus and Escherichia coli were inoculated into full‐thickness wounds prior to application of their hydrogels followed by 15 min of 808‐nm in situ light activation 110 .…”
Section: Nir and Longer Light‐activated Materialsmentioning
confidence: 99%
“…Owing to the good biocompatibility, biofunctional diversity, and responsiveness of peptide hydrogels, the three-dimensional network of self-assembled peptide supramolecular structures, anticancer strategies involving peptide hydrogels have great potential, either as drug carriers or as anticancer drugs being delivered to target cancer cells. Especially in the case of malignant melanoma, it would be perfect if the ACP hydrogels could serve as mechanically supportable surgical dressings for the direct treatment of tumors, preventing tumor recurrence, and promoting sizable wound healing following surgery. For large wounds or lesions near the joints, ACP hydrogels with superior mechanical properties such as tensile and mechanical stability are particularly needed to avoid the negative effects of movement. Unfortunately, most current viscoelastic peptide hydrogels are too soft for the surgical dressing purpose. , Therefore, it is important to improve the mechanical properties of ACP hydrogels.…”
Section: Introductionmentioning
confidence: 99%